Riley Lovato: capstone - Lovato, Riley, artist (Colorado State University. Libraries, 2013)
The artist's statement: What you'll find in this room is a select sampling of my work from my time spent here at Colorado State University. My time inside the art program has varied wildly, from studying Graphic Design, to Drawing, to finally finishing this semester with a BFA in Painting. Outside of the program, I finished the second degree of my double major in History in 2011. All of this growing experience and knowledge has built upon itself to shape my art, and what I find important about it. I make art is for the average viewer of my generation. Somebody who may not be well versed in art history, and may not recognize the rigorous process it can take to produce a polished result. We grew up in a world where we are constantly bombarded with flashy imagery, movie posters, and bright media. If something I've created can hold a contemporary viewer's attention for even a few moments, then I've achieved my goal. I push for capturing a sense of drama. Often, I exaggerate color, light, or contrast in order to give my work a powerful appearance which is intended to make it stand out. Very few of my pieces will sit inconspicuously on a wall. What I enjoy most however, is learning the many ways a viewer can project their own story of meaning onto an artwork. Some of my pieces take advantage of this, meant to be interpreted many different ways depending on one's perspective or background. Partly for this reason (as well as my own quest for new and exciting things), there can be little commonality found in my subject matter. From the practical joke to the serious and political, my intent is that the viewer can find a story in each painting.
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.